Environnmental and personality factors as correlates of students’ achievement in yoruba language essay writing in Oyo State (2021)
Yoruba language essay writings have attracted the interest of linguists and language educators, as observations reveal that construction of meaningful expression has become a challenge among secondary school students in recent times. Ongoing research attention has consequently been focused on a myriad of factors that could possibly explain students ’ achievement. This research, therefore, investigated environmental and personality factors as correlates of students ’ achievement in Yoruba essay writing in Oyo State. The study used survey research type of ex-post facto design; where three hundred (300) students were drawn through a multi-stage sampling procedure, from three educational zones in Oyo State. Three instruments were used to gather information: Environmental Factors Questionnaire (r=0.75); Personality Factors Questionnaires (r=0.80); and Yoruba Language Essay Writing Achievement Test (YLEWAT) (r=0.86). The data obtained were analyzed using Pearson Product Moment Correlation and Multiple regression analysis. Results of the study showed that a relationship exists between environmental variables (physical environment and classroom environment) and students’ achievement in essay writing (r=0.482, p<0.05; and r = 0.218, p<0.05, respectively). Also, all the personality variables were significantly related to achievement in Yoruba essay writing ((.r=0.140, p < 0.05); (r=0.136, p < 0.05); (r=0.144, p < 0.05) for attitude, self-efficacy and gender respectively). Furthermore, all the variables jointly explained 27.3 of the variance obser\>ed in students' achievement in Yoruba essay writing. And only the environmental variables contributed to the prediction of students ’ achievement in Yoruba essay writing (/3 = 0.433; t = 8.172; p<0.05 and ft = 0.123; t = 2.300; p<0.05, respectively for physical and classroom environments). The study recommended, among other things, that School administrators, government and parents should provide an enabling environment for the students to motivate them for learning.